Near-field enhancement of periodic nanostructures for photovoltaic applications: A theoretical study - Wang, Puqun; Azimi, Sara; Breese, Mark B. H.; Peters, Marius (Journal of Optics, 2014)
In this work, we theoretically investigate the local electric near-field distribution inside thin, nano-textured crystalline silicon (c-Si). We use rigorous wave-optical modeling to compare the impact of periodic nanostructures with different geometries on the electric near-field close to the surface. The 'nano-muffins' geometry is introduced as one example for an optical structure with promising light trapping features. By simulation, we show that this geometry features confined optical modes that create strong near-field enhancement. This enhancement is particularly beneficial for very thin c-Si solar cells and is investigated in detail. The nano-muffins structure can achieve an average of 29-fold near-field enhancement in the spectrum of interest for silicon photovoltaic applications, which is comparable to the enhancements achievable with plasmonic structures. Furthermore, we demonstrate that the near-field enhancement with nano-muffins can be achieved over a broad spectral range, which is a marked advantage of dielectric structures over plasmonic structures. The presented findings are of potential interest also for other optoelectronic devices, such as LEDs or sensors.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Light management; Nanostructure; Near-field; Optical modes; Photovoltaic